Reduced space in outdoor feedlot impacts beef cattle welfare - Macitelli, F.; Braga, J. S. [UNESP]; Gellatly, D.; Paranhos da Costa, M. J.R. [UNESP] (Elsevier, 2020)
There is a trend to reduce the space allowance per animal in cattle feedlot, despite its potential negative impact on animal welfare. Aiming to evaluate the effects of space allowance per animal in outdoor feedlots on beef cattle welfare, a total of 1350 Nellore bulls (450 pure and 900 crossbred) were confined for 12 weeks using three space allowances: 6 (SA6), 12 (SA12) and 24 (SA24) m2/animal (n = 450 per treatment). Bulls were housed in three pens per treatment (n = 150 per pen). The first 6 weeks in the feedlot were defined as ‘dry’ and the last as ‘rainy’ period, according to the accumulated precipitation. Animal-based (body cleanliness, health indicators and maintenance behaviour) and environmental-based indicators (mud depth and air dust concentration) were assessed weekly during the feedlot period. Most of the health indicators (nasal and ocular discharge, hoof and locomotion alterations, diarrhoea, bloated rumen and breathing difficulty) were assessed in a subset of 15 animals randomly selected from each pen. Coughs and sneezes were counted in each pen. Maintenance behaviours (number of animals lying and attending the feed bunk) were recorded with scan sampling and instantaneous recording at 20-min intervals. Postmortem assessments were carried out in all animals by recording the frequencies of macroscopic signs of bronchitis, pulmonary emphysema, nephritis and urinary cyst and by measuring the weight and cortical and medullar areas of adrenal glands (n = 30 per pen). Compared with SA12 and SA24, SA6 showed a greater number of sneezes per minute during the dry period and a greater percentage of animals with locomotion alterations during the rainy period. Coughing, diarrhoea and nasal discharge affected a larger number of animals in the SA6 relative to the other two groups. During the rainy period, there was a lower percentage of animals with nasal and ocular discharge, and a greater percentage of animals with abnormal hoof and lying. A lower percentage of animals in SA6 and SA12 (but not SA24) attended the feed bunk during the rainy relative to the dry period. A mud depth score of 0 (no mud) was most frequent in SA24 pens, followed by SA12 and then SA6. Adrenal gland weight and cortical area were lower in SA24 animals compared with those in SA6 and SA12. The results show that decreasing the space allowance for beef cattle in outdoor feedlots degrades the feedlot environment and impoverishes animal welfare.
Keywords: bovine; comfort; health; housing; stress